"The More the Better" Paradox of Antenatal Ultrasound Examinations in Low-Risk Pregnancy. Issue 10 (October 2016) - Chiossi, Giuseppe; Palomba, Stefano; Balduzzi, Sara; Costantine, Maged M.; Falbo, Angela I.; La Sala, Giovanni B.
Abstract : (Abstracted from Am J Perinatol 2016;33:646–657) The increasing rates of cesarean delivery (CD) worldwide have caused concern regarding maternal risks in subsequent pregnancies, higher neonatal and childhood morbidity, and increased health care costs. The identification of modifiable risk factors for CD and operative vaginal deliveries has therefore assumed importance.